COMPUTER ILLUSTRATION AND COMPUTER VISUALIZATION IN TEACHING PROCESS - SEDIVY, Josef (Journal of Technology and Information Education, 2009)
The article shows didactical possibility of computer vizualization methods and computer illustration methods and tools, application in the teaching process of technical subjects. This computers tools have to be a current part of the evalution and elaboration of students measurements, experiences, researches and projects. Scientific vizualization methods and their application by means of information technology aks for greated attention of the teachers of technical subjects. More supporting of computer hardware and software improve quality and accessibility visualisation. tools.
Keywords: computer vizualization; information technology; teaching process of technical subjects